Evaluation of water quality in the swamp river border using water quality index - Alvian Febry Anggana; Pranatasari Dyah Susanti (Journal of Degraded and Mining Lands Management, 2020)
As a source of minerals, water must be continuously maintained, including in term of its quality. Meanwhile, swamps are wetlands that have the potential to experience a decline in water quality. The presence of river borders in swamps has been known to maintain their water quality. Vegetation cover of the river border is established through restoration activities in which it is expected, directly and indirectly, to improve water quality. This study aimed to investigate the water quality in swamp using the Water Quality Index (WQI). Surveys were carried out and samples were collected to determine the effect of restoration on river border in swamps. Samples were collected severally, namely prior to restoration (T0), first year (T1), third year (T3) and fourth year (T4) after restoration. The parameters for water quality of T0 and T1 include pH, DO, BOD, TDS, turbidity and nitrate, while for T3 and T4 include: pH, DO, BOD, TDS, temperature, phosphate, E. coli and nitrate. The findings indicated that the WQI of the swamp prior to restoration was greater than that at the first year of restoration due to the process of land clearing. Meanwhile, the WQI at the third year has improved compared to before the restoration and land clearing phase. It suggests that the presence of vegetation on river border is able to improve the water quality. At the fourth year, a fire in the upstream reached the area adjacent to the study site. It led to a decline in surface water quality and affected the water quality index. Furthermore, the abundance of aquatic biota was indicated by two taxa of zooplankton in the third year of restoration while none of them was identified in the fourth year. In overall, restoration activities on the river border improve the quality of water in swamps in a sustainable manner.